2019
DOI: 10.22175/mmb2019.07.0024
|View full text |Cite
|
Sign up to set email alerts
|

Visual Degree of Doneness Impacts Beef Palatability for Consumers with Different Degree of Doneness Preferences

Abstract: The objective of this study was to determine the impact on beef palatability perceptions when consumers with varying degree of doneness (DOD) preferences are served steaks cooked to multiple DOD. Paired Low Choice strip loin steaks were randomly assigned to a DOD of either rare (60°C), medium-rare (63°C), medium (71°C), medium-well (74°C), or well-done (77°C). Consumer panelists were prescreened for DOD preference (rare, medium, or well-done) prior to sensory panels and were assigned to panels based on their D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
3
6
1
1
Order By: Relevance
“…This is supported by results from Prill, Drey, Olson, et al. (2019) who found that consumers who order their steaks well‐done, changed their score substantially based on the lighting scenario, indicating that the emotional disliking to the bloodlike appearance (of cooked meat exudate) plays a large role in consumer perception. These two studies can be related to Figure 2 and confirm how expectations and situational variables affect the consumption behaviors of consumers.…”
Section: Effect Of Degree Of Doneness On the Sensory Properties Of Meatsupporting
confidence: 56%
See 3 more Smart Citations
“…This is supported by results from Prill, Drey, Olson, et al. (2019) who found that consumers who order their steaks well‐done, changed their score substantially based on the lighting scenario, indicating that the emotional disliking to the bloodlike appearance (of cooked meat exudate) plays a large role in consumer perception. These two studies can be related to Figure 2 and confirm how expectations and situational variables affect the consumption behaviors of consumers.…”
Section: Effect Of Degree Of Doneness On the Sensory Properties Of Meatsupporting
confidence: 56%
“…This is especially true for color evaluation by a trained panel. When sensory evaluation is conducted by a trained sensory panel, red filtered lights are commonly used to mask the color differences (Ares & Varela, 2017; Lucherk et al., 2016; Prill, Drey, Olson, et al., 2019).…”
Section: Effect Of Degree Of Doneness On the Sensory Properties Of Meatmentioning
confidence: 99%
See 2 more Smart Citations
“…In consumer research conducted at Kansas State University, participating consumers are commonly asked about their purchasing motivators. These research studies indicated midwestern consumers placed the importance of the nutritive value of meat from 52 to 55 on a 100-point scale with 100 designated as being extremely important (Wilfong et al, 2016a(Wilfong et al, , 2016bVierck et al, 2018;Olson et al, 2019;Prill et al, 2019). In Europe, Wezemael et al (2014) reported consumers valued meat nutritional claims based on country.…”
Section: Introductionmentioning
confidence: 99%